PKM PEMBINAAN STRATEGI TEKNOLOGI INFORMASI DAN BAHASA INGGRIS UNTUK PEMASARAN DAERAH WISATA KAMPUNG TUA NONGSA KOTA BATAM - Pastima Sima; Nurma Dhona Handayani; Siska Damayanti (JURNAL PADI (Pengabdian mAsyarakat Dosen Indonesia), 2019)
Batam is one of the areas surrounded by a cluster of islands around it. In addition, the location of Batam, which is one of the gates in the interaction of international trade, is also a major advantage in supporting the economy of the people who live in the Batam area and its surroundings. As an archipelago, Batam has tourist attractions that attract visitors or foreign tourists. most of the tourist attractions which are the destination for local tourists and foreign tourists are the islands around Batam. Most of the people or residents who live on these islands earn income by utilizing abundant marine products. With the existence of tourist destinations around the islands around Batam, many people try to take advantage of these situations and conditions by providing simple dwellings for tourists visiting the area. In addition to housing, the community also prepares culinary tourism destinations for visitors who offer typical cuisine and food products from the area, which are mostly marine products. Therefore, in its efforts to increase the attractiveness of visitors, it will be very important for the people who reside and manage their own businesses to be able to communicate well to every local and foreign tourist. With good language skills, especially the ability to use English, this can help increase visitor attraction and is a good strategy for the community to be able to improve their quality so that the sea products managed by the community are getting better.